AB0692 Effects of intravenous golimumab on patient-reported outcomes in active ankylosing spondylitis: 28-week results of the phase III go-alive trial. (15th June 2017) - Reveille, JD; Deodhar, A; Chan, EK; Peterson, S; Li, N; Hsia, E; Kim, L; Lo, KH; Harrison, DD; Han, C
Abstract : Objectives: To evaluate patient-reported outcomes (PRO) of physical functioning, mental health functioning, health state, and health-related quality of life (HRQoL) in patients (pts) w/active Ankylosing Spondylitis (AS) treated w/intravenously administered (IV) golimumab (GLM), an anti-TNFα monoclonal antibody. Methods: GO-ALIVE is a Phase 3, multicenter, randomized, double-blind, placebo-controlled trial. Pts (aged ≥18 years) had a diagnosis of definite AS (per modified New York criteria) and BASDAI ≥4, total back pain visual analogue scale ≥4, and CRP ≥0.3mg/dL. At baseline, 208 pts were randomized either to IV GLM 2mg/kg (N=105) at Wks 0, 4, and every 8 wks or placebo (PBO, N=103) at Wks 0, 4, and 12, w/crossover to GLM at Wk 16. Three PRO instruments were included: 1) SF-36, a generic instrument designed to measure physical & mental health functioning, 2) EQ-5D visual analogue scale (VAS), a generic measure of current health state & 3) Ankylosing Spondylitis Quality of Life (ASQoL) questionnaire, a disease-specific instrument designed to measure the impact of AS on HRQoL. The scores for SF-36 range from 0–100 w/higher scores indicating better functioning. It has Physical (PCS) and Mental Component Summary (MCS) and eight subscales (physical functioning, role-physical, body pain, general health, vitality, social functioning, role-emotional, & mental health). EQ-5D has a scale of 0–100 (0=worst health you can imagine to 100=best health you can imagine). ASQoL assesses sleep, mood, motivation, ability to cope, activities of daily living, independence, relationships, & social life in pts w/AS. The scores range from 0–18 w/higher scores indicating worse HRQoL. Unadjusted p-values of least square mean differences (LSMD) between treatment groups were based on analysis of covariance (ANCOVA) controlling for prior anti-TNF therapy. Results: Table 1 summarizes the mean changes from baseline at Wks 8, 16, & 28. Improvements from baseline in SF-36 PCS & MCS were greater in the GLM group than PBO at Wk 8 (6.83 vs. 2.07, p<0.001; 5.56 vs. 1.67, p=0.006, respectively) and maintained through Wk 16 (8.52 vs. 2.87, p<0.001; 6.47 vs. 0.84, p<0.001, respectively). Improvements in all SF-36 subscales were observed in the GLM group at Wks 8 & 16 compared to PBO (p<0.01, with the exception of the role-emotional subscale [p=0.058]). The percentage of pts achieving clinically meaningful change (5 points or greater) in SF-36 PCS & MCS were higher in GLM than PBO in Wks 8 & 16 (PCS: 58.1 vs. 27.2, 67.6 vs. 35.9, respectively; MCS: 48.6 vs. 34.0, 54.3 vs. 29.1, respectively; p<0.05 for all). Mean EQ-5D VAS improvements were greater (p<0.001) in GLM than PBO at Wks 8 & 16 (17.61 vs. 6.63, 20.32 vs. 4.79, respectively). Greater improvements in ASQoL were observed in GLM compared to PBO at Wks 8 & 16 (-4.5 vs. -1.5, p<0.001, -5.4 vs. -1.8, p<0.001, respectively). By Wk 28, after PBO crossed-over to GLM, improvement in PCS, MCS, EQ-5D VAS, & ASQoL were similar between the two treatment arms. Conclusions: Adult pts w/active AS treated w/IV GLM showed marked improvements in physical functioning, mental health functioning, health state, & HRQoL. Disclosure of Interest: J. Reveille Grant/research support from: Janssen Scientific Affairs, LLC., A. Deodhar Grant/research support from: Janssen, Amgen, Abbvie, GSK, Eli Lilly, Novartis, Pfizer, UCB, Consultant for: Janssen, Eli Lilly, Novartis, Pfizer, UCB, E. Chan Employee of: Janssen Global Services, LLC, S. Peterson Employee of: Janssen R&D, LLC, N. Li Employee of: Janssen R&D, LLC, E. Hsia Employee of: Janssen R&D, LLC, L. Kim Employee of: Janssen R&D, LLC, K. H. Lo Employee of: Janssen R&D, LLC, D. Harrison Employee of: Janssen R&D, LLC, C. Han Employee of: Janssen Global Services, LLC